Strengthening Religious, Personal, Human, Natural and State Character Based on Integrative Morals in Elementary Schools in Makassar City - Suardi Suardi; Nursalam Nursalam; Israpil Israpil (STAI Hubbulwathan Duri, 2023)
The main problem in this study is the poor behaviour of students still experiencing decadence. The study aimed to produce a model for strengthening character education based on moral integration for elementary school students in the Teaching Campus Classes 1 and 2 in 2021 during the COVID-19 pandemic in Makassar City. This study uses mixed research methods, data collection techniques using questionnaires, observations, interviews and documentation, then analyzed qualitatively and quantitatively. The results show that strengthening good character in religion, personally, among fellow human beings, towards nature and in the state is in an outstanding category at all stages of moral knowing, feeling, sinverbal, action, habitus and culture from various campus teaching activities such as teaching assistants , activities for dhuha and dhuhur prayers, counselling guidance activities, flag ceremony activities, activities to clean the room and school environment, activities to recycle waste or used goods, and the use of Indonesian in the school environment. These activities are integrated into intra-curricular, co-curricular, and non-curricular and extra-curricular activities involving school principals, teachers (classes, subjects, counselling guidance), students, lecturers and parents. Strengthening the character profile of Pancasila students in Campus Teaching activities is carried out based on moral integrative and social collaboration.